2006
DOI: 10.1021/ja0643164
|View full text |Cite
|
Sign up to set email alerts
|

Catalytically Induced Electrokinetics for Motors and Micropumps

Abstract: We have explored the role of electrokinetics in the spontaneous motion of platinum-gold nanorods suspended in hydrogen peroxide (H2O2) solutions that may arise from the bimetallic electrochemical decomposition of H2O2. The electrochemical decomposition pathway was confirmed by measuring the steady-state short-circuit current between platinum and gold interdigitated microelectrodes (IMEs) in the presence of H2O2. The resulting ion flux from platinum to gold implies an electric field in the surrounding solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
494
1
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(528 citation statements)
references
References 30 publications
27
494
1
6
Order By: Relevance
“…Both free energies have to have the same form as (4), since that form is required by rotation invariance, but the Frank constants K 1,2,3 that appear in them need not be equal.…”
Section: Hydrodynamics Of Active Nematicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both free energies have to have the same form as (4), since that form is required by rotation invariance, but the Frank constants K 1,2,3 that appear in them need not be equal.…”
Section: Hydrodynamics Of Active Nematicsmentioning
confidence: 99%
“…We now justify the isotropic viscosity approximation. In the limit of weak order, which in the notation of Kuzuu and Doi [32] is the limit S 2 ,S 4 1, our isotropic viscosity approximation becomes valid because α 4 (our activity parameter α should not be confused with Kuzuu and Doi's anisotropic viscosities), which is just the isotropic piece of the viscosity, is much greater than the anisotropic pieces α 1,5,6 of the viscosity, since the latter all vanish when S 2,4 → 0, with (again in the notation of Kuzuu and Doi) η = α 4 /2 ≈ η * C 3 r 2 . Furthermore, the coefficient γ 1 = α 3 − α 2 = 10η * C 3 r 2 S 2 /λ.…”
Section: Appendix B: Justification Of the Frozen Director And Isotropmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts in this area range from synthetic modifications on existing biomotors [1][2][3][4][5] to purely synthetic catalytic bimetallic nanomotors [5][6][7][8]. Motion of the synthetic motors has been achieved using a number of propulsion mechanisms including autodiffusiophoresis [9][10][11], autoelectrophoresis [6,7,[12][13][14], and bubble generation [15,16]. There are numerous reviews of motors and we point to Ebbens and Howse [17] for a general review of motors and to Paxton, Sen, and Mallouk [7] or Wang [18] for reviews of self-electrophoretic motors.…”
Section: Introductionmentioning
confidence: 99%
“…When a magnetic field was applied, the rod could be aligned perpendicular to the magnetic field and moved in the direction of the platinum end. Paxton et al [74] focused on the mechanism of the moving. They suggested that the movement was caused by the electro kinetic phenomenon.…”
Section: Propulsion By Chemical Reactionmentioning
confidence: 99%